Extrapulmonary Tuberculosis Mimics Diffuse Metastatic Disease: A Case Report - Gulgun Engin; Kızıldag Yirgin; Hulya Kandemir (Indian Journal of Radiology and Imaging, 2021)
Background Extrapulmonary tuberculosis (TB) is associated with major diagnostic difficulties as it has many atypical symptoms and its imaging findings are similar to those of many other diseases.